MODEL PENGEMBANGAN BUDAYA MUTU MADRASAH BERBASIS NILAI-NILAI KEPESANTRENAN - Agus Prayitno; Somantri Somantri; Muhamad Syakuri (Universitas Islam Bunga Bangsa Cirebon, 2022)
Madrasah as Islamic educational institutions in Indonesia faces a persistent challenge in building a sustainable quality culture that is simultaneously aligned with modern educational standards and rooted in its distinctive Islamic identity. This study aims to construct a conceptual model of madrasah quality culture development grounded in pesantren-based values, encompassing ikhlas (sincerity), tawadhu (humility), ukhuwah (brotherhood), tafaqquh fi al-din (deep religious understanding), and istiqamah (consistency). Employing a systematic library research methodology, this study analyzed authoritative books published within the last five years and reputable peer-reviewed articles indexed in Scopus and national accredited journals. Findings reveal that pesantren values are not merely spiritual ornaments but serve as structural pillars of an authentic quality culture that shapes collective behavior, strengthens organizational commitment, and drives continuous improvement. The proposed model integrates five interconnected dimensions: value internalization, leadership exemplification, systemic habituation, reflective evaluation, and sustainable renewal. This framework offers practical and contextually grounded guidance for madrasah principals and educational policymakers seeking to strengthen institutional quality from within.